Minimize the impact of waste pollution in ship repair processes to Improving Shipyard Industrial Infrastructure Sustainability - Rachmat Ashari (E3S Web of Conferences, 2018)
Increasing the number of ship repair that make improvements it can be ensured that the greater the level of pollution will occur. Facilities (Infrastructure) is very helpful to minimize the pollution that will occur when ship repair. If the conditions of Infrastructure make it possible to flourish nowadays, which will further improve environmental performance. Development to improve domestic shipyard Infrastructure sustainability is very importance since 20% of national ship repair is still undertaken in foreign shipyard. This indicates that the ability of national shipyards still need to be improved especially in the infrastructure and facilities sector as production supports. This paper used data sample was undertaken in State-Owned Shipyard industry located in North Jakarta. Data analysis was undertaken starting from the ship entry, repair process until the accomplishment of ship repair. This research is testing the chemical impacts with related chemical parameters around the shipyard. the results showed that dangerous chemical concentrations were located around the shipyard and threatened the surrounding aquatic ecosystems. there needs to be management of shipbuilding infrastructure management that can minimize hazardous waste, especially basic storage. Basically the improvement of shipyard infrastructure can be undertaken if the ship repair process keeps increasing.